The contribution of facial regions to judgements of happiness and trustworthiness from dynamic expressions - Calvo, Manuel G; Álvarez-Plaza, Patricia; Fernández-Martín, Andrés (Journal of Cognitive Psychology, 2017)
What expressive facial features and processing mechanisms make a person look trustworthy, relative to happy? Participants judged the un/happiness or un/trustworthiness of people with dynamic expressions in which the eyes and/or the mouth unfolded from neutral to happy or vice versa. Faces with an unfolding smile looked more trustworthy and happier than faces with a neutral mouth, regardless of the eye expression. Unfolding happy eyes increased both trustworthiness and happiness only in the presence of a congruent unfolding smiling mouth. Nevertheless, the contribution of the mouth was greater for happiness than for trustworthiness; and the mouth was especially visually salient for expressions favouring happiness more than trustworthiness. We conclude that the categorisation of facial happiness is more automatically driven by the visual saliency of a single feature, that is, the smiling mouth, while perception of trustworthiness is more strategic, with the eyes being necessarily incorporated into a configural face representation.
Keywords: facial expression; trustworthiness; happiness; smile; visual saliency; JCR; Scopus